Sosialisasi Pendaftaran Tanah Sporadik di Desa Kedungbanteng Kabupaten Tegal - Soesi Idayanti; Evy Indriasari; Moh.Taufik; Sugiyanto Sugiyanto; Sanusi Sanusi (Pusat Riset dan Inovasi Nasional, 2025)
For individuals and legal entities, land registration serves as the sole method to protect land ownership and ensure legal certainty. The foundation of land rights is based on Law No. 5 of 1960 concerning the Basic Agrarian Principles, which recognizes several types of land rights, including Ownership Rights (Hak Milik), Building Use Rights (Hak Guna Bangunan), Cultivation Rights (Hak Guna Usaha), and Use Rights (Hak Pakai). The primary objective of this Community Service Program (Pengabdian kepada Masyarakat or Abdimas) is to educate the public and clarify misinformation circulating on social media. The educational initiative focuses on Government Regulation No. 18 of 2021, which ensures that long-standing land rights can still be registered through the “Recognition of Rights” mechanism. This discussion activity was initiated by the Faculty of Law, Universitas Pancasakti Tegal, which felt compelled to engage with the community in addressing issues related to land ownership and registration. Through this initiative, is hoped that public awareness and understanding of land law can be significantly improved.